2022
DOI: 10.1186/s12711-021-00693-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Swedish Warmblood fragile foal syndrome carriers and breeding prospects

Abstract: Background Warmblood fragile foal syndrome (WFFS) is a monogenetic defect caused by a recessive lethal missense point mutation in the procollagen‐lysine, 2‐oxoglutarate 5‐dioxygenase 1 gene (PLOD1, c.2032G>A). The majority of homozygous WFFS horses are aborted during gestation. Clinical signs of affected horses include fragile skin, skin and mucosa lacerations, hyperextension of the articulations, and hematomas. In spite of its harmful effect, a relatively high frequency of WFFS carriers has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Despite its harmful effect, a relatively high frequency of FFS carriers (7.4%) was found in the Swedish Warmblood breed (SWB), suggesting the presence of a heterozygous advantage. The presence of balancing selection in SWB was corroborated in a recent study where significant positive effects of the FFS allele were found mainly on movement related traits (Ablondi et al, 2022). Balancing selection causes various types of signatures in the genome such as: increased diversity around the target of selection, differentiation between populations departing from the same genome wide background, and increased linkage disequilibrium around the target of selection (Fijarczyk and Babik, 2015).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Despite its harmful effect, a relatively high frequency of FFS carriers (7.4%) was found in the Swedish Warmblood breed (SWB), suggesting the presence of a heterozygous advantage. The presence of balancing selection in SWB was corroborated in a recent study where significant positive effects of the FFS allele were found mainly on movement related traits (Ablondi et al, 2022). Balancing selection causes various types of signatures in the genome such as: increased diversity around the target of selection, differentiation between populations departing from the same genome wide background, and increased linkage disequilibrium around the target of selection (Fijarczyk and Babik, 2015).…”
Section: Introductionmentioning
confidence: 57%
“…In NS horses, we found a haplotype block containing the FFS variant which was not detected in the SJ horses. A potential reason behind the failure to detect the haplotype in the SJ may be the lower frequency (5.8% in SJ vs 14.6% in NS) of the FFS variant in SJ horses as previously found by Ablondi et al (2022) or that the selection pressure for heterozygosity in PLOD1 is lower in SJ horses. In NS horses, the FFS variant was in strong LD with a SNP located within the Mitofusin 2 (MFN2) coding gene.…”
Section: Discussionmentioning
confidence: 92%
“…It is also important to take notice to traits that have a linear relationship with performance, because selection towards more extreme expression of certain traits may have negative consequences on the welfare of the horse. For example, it has been shown that horses that are carriers of the Fragile Foal Syndrome mutation have more elastic trot than non-carriers, indicating that breeding for that trait could increase the prevalence of the deleterious mutation in the population (Ablondi et al, 2022). Thus, monitoring of health and durability in the population is highly recommended, which would require cooperation between the breeding organization, veterinarians, insurance companies, and horse owners.…”
Section: Practical Implications For Breedingmentioning
confidence: 99%
“…A likely causal variant is known in 99 of these traits or disorders, where 54% of them represent coat colours, 41% are disease-causing variants, and 4% of the variants are associated with performance traits. Among the most recent studies of important monogenic diseases are Fragile Foal Syndrome (Ablondi et al 2022), Dwarfism and joint laxity in Frieasian horses (Leegwater et al 2016), and Ocular Squamous Cell Carcinoma (Chen et al 2021).…”
Section: Important Monogenic and Multifactorial Diseases And Traits I...mentioning
confidence: 99%